2016
DOI: 10.1039/c5sc03436a
|View full text |Cite
|
Sign up to set email alerts
|

Water opens the door to organolithiums and Grignard reagents: exploring and comparing the reactivity of highly polar organometallic compounds in unconventional reaction media towards the synthesis of tetrahydrofurans

Abstract: Grignard and organolithium reagents undergo smooth nucleophilic additions to γ-chloroketones “on water”.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
48
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 109 publications
(52 citation statements)
references
References 61 publications
2
48
0
2
Order By: Relevance
“…[7] As an opening gambit towards this target, we recently pioneered use of green and biorenewable deep eutectic solvents (DESs) combining ammonium salt choline chloride (ChCl) with water or glycerol (Gly) ( Figure 1) showing they can activate Grignard and organolithium reagents to promote room temperature chemoselective ketone alkylation/arylation reactions. [9] Taking organolithium DES chemistry into new,m ore taxing territory,h ere we describe the chemoselective addition of organolithium compounds to both imines and quinolines in DESs under air as an ovel sustainable methodology to amines.T his has wide implications as amine synthesis has been identified as ak ey area in green chemistry for pharmaceutical manufacturers. [9] Taking organolithium DES chemistry into new,m ore taxing territory,h ere we describe the chemoselective addition of organolithium compounds to both imines and quinolines in DESs under air as an ovel sustainable methodology to amines.T his has wide implications as amine synthesis has been identified as ak ey area in green chemistry for pharmaceutical manufacturers.…”
Section: In Memory Of Jose Barluengamentioning
confidence: 99%
“…[7] As an opening gambit towards this target, we recently pioneered use of green and biorenewable deep eutectic solvents (DESs) combining ammonium salt choline chloride (ChCl) with water or glycerol (Gly) ( Figure 1) showing they can activate Grignard and organolithium reagents to promote room temperature chemoselective ketone alkylation/arylation reactions. [9] Taking organolithium DES chemistry into new,m ore taxing territory,h ere we describe the chemoselective addition of organolithium compounds to both imines and quinolines in DESs under air as an ovel sustainable methodology to amines.T his has wide implications as amine synthesis has been identified as ak ey area in green chemistry for pharmaceutical manufacturers. [9] Taking organolithium DES chemistry into new,m ore taxing territory,h ere we describe the chemoselective addition of organolithium compounds to both imines and quinolines in DESs under air as an ovel sustainable methodology to amines.T his has wide implications as amine synthesis has been identified as ak ey area in green chemistry for pharmaceutical manufacturers.…”
Section: In Memory Of Jose Barluengamentioning
confidence: 99%
“…5 mmd iameter) and find that the cycloaddition reaction is accelerated even further (by afactor of 10 2 ) compared to that of the "on-water" reaction reported previously.T he trends of acceleration in solvents other than water demonstrated by Sharpless and colleagues were replicated in the corresponding microdroplet experiments.W ealso find that DEAD reacts with itself to form av ariety of hydrazine carboxylates and intercept intermediates of this reaction in microdroplets to validate am echanism proposed herein. [8] In almost all cases,anacceleration of several to several hundredfold has been noted relative to reactions conducted in organic solvents or even under neat conditions.M ellouli et al examined "on-water" cycloaddition reactions in biphasic microfluidic systems and investigated the role of surface-tovolume ratios on conversion rates,d emonstrating that acceleration can be ascribed to the increased rate of conversion at the surface. [1] Thes eminal discovery by Breslow and co-workers [2] of the rate acceleration of Diels-Alder cycloadditions in water suggested that the poor solubility of hydrophobic reagents may promote, rather than hamper, certain classes of reactions.I ndeed, the exploration of reactions at the organic-aqueous interface has become at opic of research in the synthetic community.…”
mentioning
confidence: 99%
“…Die Ergebnisse ließen die Schlussfolgerung zu, dass der vorliegende Lithium/Bromid-Austausch am Aromaten mindestens genauso schnell, wenn nicht sogar schneller vonstattengeht als eine konkurrierende Zersetzungsreaktion zu BuT und LiOT. [12][13][14][15][16][17][18] Darüber hinaus haben DESs eine weitreichende Anwendung in Form effektiver Elektrolytlçsungen fürS olarzellen sowie in der Biokatalyse und als Reaktionsmedium photosynthetischer Reaktionszentren im Bereich der Energietechnologie gefunden. Im Gegensatz dazu führten Versuche ohne Wasser zur signifikanten Verringerung beider Werte.…”
unclassified